The Interests of English Canada - Dan Usher (Queen's University, Department of Economics, 1993)
Recognition of conflicts of interest between French Canadians in Quebec and English Canadians in the rest of Canada is a necessary first step in the evaluation of proposals from Quebec for the refrom of the Canadian constitution, as well as for the design of institutions for an entirely English-speaking country in the event that Quebec secedes. Interests differ about the scope of bilingualism, public recognition of cultural diversity and the division of powers between Federal and provincial governments. The probability of the separation of Quebec and the potential harm to English Canadians from the retention of the Canadian constitution as it stands would seem large enough to warrant debate now among English Canadians about the appropriate form of government for a new English Canadian country.
Keywords: 330